Analisis Penerapan Strategi Bauran Pemasaran Syariah Pada Produk Tabungan Berkah Utama iB Ditengah Pandemi Covid-19 (Studi Kasus pada Bank Mega Syariah Kota Bekasi) - Achmad, Listian Indriyani; Agustin, Nur Dwi (DPPM Universitas Pelita Bangsa, 2021)
Bank Mega Syariah has a product called the iB Berkah Utama in marketing its product has ten characteristics of the Islamic marketing mix in iB Berkah Utama Savings Product namely: product, orice, place, promotion, people, process, physical evidence, promise, ptient, and customers oriented, one of the problems is people whose use of human recources is still weak and marketing of savings products, the main blessing in the iB Berkah Utama at Bank Mega Syariah amid the covid-19 pandemic, are experiencing problems/ obstacles/problems. This is reserach using a qualitative descriptive method. The methods used to obtain data sre Field Research (observation, interviews, and documentation) as supporting data Library Research. The Subjects in this study were Bank Mega Syariah Bekasi City, which included the Head of Branch, Marketing Funding and customers. The object of this research is about the strategy of the islamic marketing mix in the iB Berkah Utama Savings product Based on the results of the study, it can be concluded that employees/ Head of Branch Bank Mega Syariah who are not have an extensive network of organizations and lack of human respurces and due to the existence of health protocols, so they experience limitations in movement especially through virtual strategies, zoom meetings are felt to be less than optimal as a results the condition of customers in the midst of the Covid-19 pandemic has decreased the number of customers interest to open an iB Berkah Utama account in Bank Mega Syariah KCP Bekasi.